Kunst van de XXe eeuw in Leuvens privébezit. - Stedelijk museum, Leuven; Van Buyten, Léon (Leuven : Stadsbestuur Leuven, 1970)
Alechinsky, Pierre ; Appel, Karel ; Baes, Firmin ; Baretta, Louis ; Bertrand, Gaston ; Beullens, André ; Bogart, Bram ; Bonnet, Anne ; Boulez, Jules ; Brusselmans, Jean ; Burmester, Georg ; Camus, Gustave ; Carte, Anto ; Claus, Emile ; Creytens, Julien ; Daeye, Hyppolyte ; Dasnoy, Albert ; De Boeck, Felix ; Delvaux, Paul ; De Smet, Gustave ; etc.
Kunst van de XXe eeuw in Leuvens privébezit, Stedelijk Museum Leuven, 4 april - 30 mei 1970
boek